Cover Picture: Interactions Between Peptide Assemblies and Proteins for Medicine (Isr. J. Chem. 9‐10/2022). Issue 9 (25th October 2022) - Mañas‐Torres, Mari C.; Illescas‐Lopez, Sara; Gavira, José A.; de Cienfuegos, Luis Álvarez; Marchesan, Silvia
Abstract : The cover picture shows the interaction between the amyloid beta peptide (purple ribbon) and a self‐assembled peptide nanoparticle (pictured in gold) that results in inhibition of pathological amyloid fibrillation. This type of interaction between proteins and peptide assemblies is indeed a hot topic to find new solutions in medicine, from new vaccine adjuvants to hydrogels for tissue regeneration or for therapeutics delivery and protein crystallization. See the Review at https://doi.org/10.1002/ijch.202200018 .